(untitled) (City Dental College Journal, 2013)
Objective: The treatment of buccal gingival recession (GR) is a common requirement due to aesthetic concern, root caries and /or root hypersensitivity. The purpose of this case study was to evaluate the success and predictability of sliding pedicle graft in combination with the vestibular deepening technique for the management of Miller’s Class III gingival recession. Methods: A Saudi male adult, aged 30 years was selected having Millers Class III GR 5.0 mm on the lower left central incisor. Nonsurgical periodontal therapy was provided for the patient to ensure periodontal health. Sliding pedicle graft along with the vestibule deepening technique was applied. Patient was followed up monthly for 2 months. Results: Root coverage 60.0% and clinical attachment gain 3 mm were evident following 2 months of periodontal surgery. Conclusion: Sliding pedicle graft in combination of vestibular deepening may be applied as an effective technique to increase the width of attached gingiva and treat Class III Millers type of gingival recession. Long term continuous monitoring of the case would be conclusive. DOI: http://dx.doi.org/10.3329/cdcj.v10i2.16348 City Dent. Coll. J Voume-10, Number-2, July-2013